Authentication using Mixed-mode approach. - Urankar, Prasad N; Shete, Prasanna J (International Journal of Computer Sciences and Engineering, 2025)
Text passwords have been widely used for user authentication, e.g., by almost all websites on the Internet. However, it is well-known that text passwords are insecure for a variety of reasons. For example, users tend to choose simple passwords which can be remembered easily. In favor of memorability, making them subject to dictionary attacks; and text passwords can be stolen by malicious software (e.g., keystroke loggers) when being entered from keyboards. Phishing is another serious threat to text passwords, by which, a user could be persuaded to visit a forged website and enter their passwords. The system aim is to grant access to a legal user, and to prevent the system from illegal or non-authorized person.